Exploring the Relationship Between Career Advancement, Work-Life Balance, and Corporate Financial Performance: A Systematic Review - Samsudin, Acep; Ikaningtiyas, Maharani; Mulia, Faizal; Rintalla, Maulidya (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study explores the relationship between career advancement opportunities, work-life balance (WLB) policies, and corporate financial performance, identifying how these factors drive employee motivation and engagement to enhance organizational outcomes. A systematic review was conducted, analyzing existing literature to synthesize findings on the impact of career development and WLB policies on employee well-being, retention, and organizational performance. The review integrates relevant theories, including Herzberg's Two-Factor Theory, Human Capital Theory, Conservation of Resources Theory, and Social Exchange Theory. The study reveals clear career advancement opportunities and supportive WLB policies significantly boost employee motivation and engagement. These factors enhance job satisfaction, reduce turnover, and improve organizational performance. The findings underscore the synergistic effect of combining career development with WLB policies, creating a positive work environment that attracts and retains high-quality talent. This alignment with established theories highlights the importance of intrinsic motivators and the need for a holistic approach to human resource management. The study provides practical insights for organizations to integrate career advancement and WLB policies into their strategic planning, fostering a culture that values employee development and well-being. This approach enhances employee satisfaction and retention and strengthens the organization's competitive edge. Future research should focus on exploring these dynamics across different industries and contexts, considering cultural and regional differences to optimize the effectiveness of these strategies.